2011
DOI: 10.2147/tcrm.s13883
|View full text |Cite
|
Sign up to set email alerts
|

Naftopidil for the treatment of urinary symptoms in patients with benign prostatic hyperplasia

Abstract: Naftopidil, approved only in Japan, is an α1-adrenergic receptor antagonist (α1-blocker) used to treat lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH). Different from tamsulosin hydrochloride and silodosin, in that it has higher and extremely higher affinity respectively, for the α1A-adrenergic receptor subtype than for the α1D type, naftopidil has distinct characteristics because it has a three times greater affinity for the α1D-adrenergic receptor subtype than for the α1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…Naftopidil (NAF; R,S-1-(4-(2-methoxyphenyl)-1-piperazinyl)-3-(1-naphthyloxy)-2-propanol) is a specific subtype of selective ␣ 1 -adrenoceptor blocker frequently used for LUTS/BPH treatment [4,5]. Previous studies have shown that NAF exhibits superior efficacy compared with other ␣ 1 -adrenoceptor blockers, such as tamsulosin, and incidence rates of ejaculatory disorders and intraoperative floppy iris syndrome induced by NAF are lower than those induced by tamsulosin and silodosin [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Naftopidil (NAF; R,S-1-(4-(2-methoxyphenyl)-1-piperazinyl)-3-(1-naphthyloxy)-2-propanol) is a specific subtype of selective ␣ 1 -adrenoceptor blocker frequently used for LUTS/BPH treatment [4,5]. Previous studies have shown that NAF exhibits superior efficacy compared with other ␣ 1 -adrenoceptor blockers, such as tamsulosin, and incidence rates of ejaculatory disorders and intraoperative floppy iris syndrome induced by NAF are lower than those induced by tamsulosin and silodosin [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…8 However, the study was carried out as a retrospective study using naftopidil, which has a threefold higher affinity for a1D than for the a1A subtype and is only available in Japan. 12 Thus, in the present study, we prospectively evaluated what percentage of patients dropped out during a 5-year follow-up period after administration of tamsulosin, which has a threefold higher affinity for a1A than for the a1D subtype and is universally available, and the reasons why they terminated medication, including patients who were lost to follow up. In addition, static and dynamic variables to predict treatment failure and conversion to surgery were determined, as well as the long-term efficacy and safety of tamsulosin.…”
Section: Introductionmentioning
confidence: 99%
“…Naftopidil was approved at an OD dosage [2]. Generally, OD dosing contributes to improved drug compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it shows fewer adverse effects related to blood pressure [1]. The effects of naftopidil are dose-dependent, and the optimal dosage for the treatment of LUTS associated with BPH (LUTS/BPH) in Japan is recommended to be from 25 mg/day to 75 mg/day [2].…”
Section: Introductionmentioning
confidence: 99%